GENDER, CULTURE, AND CHANGE: A CRITICAL ANALYSIS OF WOMEN’S ROLES IN TRIBAL SOCIETIES - Precious Star Tmung (IJRDO - Journal of Social Science and Humanities Research, 2026)
Since the dawn of civilization, women have always been taken for granted. They were treated as inferior to men and there were times when they were considered to be just the property of men. The subjugation of women can be seen in all spheres of life be it in the family, the society, politics, economy and even in the church. The Tribal Society in the North East which to the eyes of the outsider is one of the most progressive in terms of women empowerment. Majumdar, while dealing with the status of Tribal women states that “the rigid codes of behaviour which outlined for women in Brahmanical texts do not affect Tribal and lower caste women”.[1] Even though it is very clear that Tribal Women are not bound by the codes of Brahmanical texts, yet one cannot say that all tribal women are treated the same way in their own societies. O. L. Snaitang states “Though women played an important role in the structure of the society, they were not necessarily highly regarded or permitted freedom of actions as persons”.[2] When it comes to the status of women in the Tribal Society, there are two dominant views: one view suggests that men and women in the tribal society enjoy equal status whereas the second view is of the opinion that women occupy the lower status in tribal societies. Such being the case, it is very difficult to say whether women are really enjoying equal rights/ status in Tribal societies or are they being treated as subordinate to men?. In order to be able to understand the real position of women in the Tribal Society, this paper will try to bring out the economic condition of Tribal women and their involvement in the economy of the society and will also try to draw ways and means as to how women can be empowered and helped so that they can be economically independent and live life to its fullness.